Pidżyny i inne języki wehikularne - Barbara Hlibowicka-Węglarz (Ksiegarnia Akademicka Publishing, 2017)
Pidgins and Other Vehicular Languages Vehicular languages are languages which are used as a mean of communication in multicultural and multilingual societies; therefore the key to understanding the essence of vehicular languages is to analyse linguistic contact. The purpose of this study is to analyse such vehicular languages as: pidgin, lingua franca, and sabir, as well as to present the similarities and differences between them. An additional goal is to show the different types of vehicular languages which were used all around the world.